A CAUSAL ANALYSIS OF THE DEFENCE-GROWTH RELATIONSHIPS: EVIDENCE FROM THE BALKANS - Georgantopoulos, Andreas G. (European Scientific Journal, ESJ, 2012)
The causal relationships between military burden and economic growth have attracted considerable interest of academics, scholars and practitioners during the last three decades. This survey is hoping to contribute to the existing pool of literature by investigating the causal links between defence spending and economic growth for three developing Balkan countries (Bulgaria, Romania and Albania) and their mature counterpart in the Balkan Peninsula (Greece) during the period 1988-2009. Empirical results imply that there are no bilateral links between the tested variables for any of the tested countries. However, findings indicate the presence of one-way causal links running from military expenditures to GDP only for Bulgaria and Albania, implying the significant impact of defence burden on growth for these countries. On the other hand, empirical results for Greece and Romania suggest that defence spending and GDP growth are independent, which favours neutrality hypothesis. Nevertheless, it should be mentioned that we would expect to find significant links especially in the case of Greece, due to the fact that the country presents the highest defence expenditures in the Balkan region for the last fifteen years. These contradictory results could be due to different levels of maturity between the tested countries but it could also be attributed to temporary changes of accounting practises (i.e. recording expenses when military material was ordered rather than received, as evidenced in the case of Greece in the late 1990’s by government officials). These accounting changes could be the obstacle in some cases (e.g. Greece) to provide empirical evidence of the links between defence burden and economic growth.